Analysis of Digital Bank Company Value on the Indonesian Stock Exchange - Al Hafis, M.; Nawir, Jubaedah (KnE Social Sciences, 2024)
This study investigates how growth opportunity, investment opportunity set, and company size impact the valuation of digital banks that are publicly traded on the Indonesian Stock Exchange from 2018 to 2022. The sample selection method employed was full sampling, consisting of 13 companies as samples, and panel data regression analysis was utilized in this study with the assistance of E-views 12 software. According to the research findings, there are several discoveries. First, growth opportunities do not affect company value. Second, investment opportunity sets do affect company value. Third, the company size affects company value. Keywords: growth opportunity, IOS, ompany size, company value